Statistical Machine Translation Using Labeled Semantic Dependency Graphs - Aue, Anthony; Menezes, Arul; Moore, Bob; Quirk, Chris; Ringger, Eric (ACL/SIGPARSE, 2004)
We present a series of models for doing statistical machine translation based on labeled semantic dependency graphs. We describe how these models were employed to augment an existing example-based MT system, and present results showing that doing so led to a significant improvement in translation quality as measured by the BLEU metric.